Persebaran Penyakit di Kawasan Laut Jawa Abad XIX - XX - Didik Pradjoko; Imas Emalia (Universitas Negeri Padang, 2021)
This article discussed about the process of diseases spreading along the Java Sea area during the 19th and the early 20th century. This study utilized historical method with an aim to reconstruct past events, especially on the outbreaks happened in the Java Sea area and how the colonial governmnet dealt with the occurrence. The article applied Braudel’s structural theory (1988) to analyze the existence of structures, which were taking a role in the process of diseases spreading. This analysis was supported by the concept of ‘silent barter’, developed by Knapen (1995) as a benchmark to determine factors that caused the spread. The results allowed us to discover that the dynamics of shipping and trading in the Java Sea at that time were part of the whole pandemic situation. There were at least two diseases discussed as the main focus of this article, smallpox and cholera, as these two severely affected the trading and shipping activity. These diseases were carried by the crews of ships escaping the quarantine doctors who carried out medical examination at various ports. Several ports in Java, such as Batavia, Semarang, Cirebon, and Surabaya, had become the epicenters of the outbreak. The government applied a regulation to attached a yellow flag to the ship contaminated by the plague before they entered the port area. The yellow flag functioned as an identifying marker. The regulation was supposed to limit the spread of diseases from the coastal area of Java to the mainland, as well as to gain more attention from other ships and doctors resided near the ports. The yellow flag system made it easier for the government and doctors to handle smallpox and cholera outbreaks, even though there had been some aberrations in economic activities in this area.